The Jawz Valley. Reconstructing an Ottoman 'waterscape' in Mount Lebanon. (4th May 2019) - McPhillips, Stephen; Meier, Astrid; Slim, Souad; Bradbury, Jennie
Abstract : Mount Lebanon, with its complex topography, abundance of water and often dense vegetation cover, has rarely featured in the new and growing field of medieval and Ottoman archaeology of the Levant. The historiography of Lebanon, by contrast, is rich and varied for this period, and addresses rural communities directly. This contribution presents the first results of cross-disciplinary research on a case study, the Jawz Valley, in northern Lebanon. It sets out to reconstruct the essential elements of this waterscape during the Ottoman period. The relationships between hydro-agricultural remains, settlement patterns and shifting or overlapping scales of administration and control of water-related infrastructure are a critical factor in establishing a diachronic perspective of social, economic and political continuity and rupture in this landscape.